Chemometric profiling of metabolites in Avicennia marina leaves from various locations in Indonesia - FEBRIANSYAH HANIK DWI SAPUTRI; EKO SUSANTO; ANINDITIA SABDANINGSIH (Society for Indonesian Biodiversity, 2026)
Abstract. Saputri FHD, Susanto E, Sabdaningsih A. 2026. Chemometric profiling of metabolites in Avicennia marina leaves from various locations in Indonesia. Biodiversitas 27 (1): d270139. https://doi.org/10.13057/biodiv/d270139. Avicennia marina is a mangrove species that thrives in extreme environments and produces various metabolites. This study analyzes variation in the secondary metabolite profiles of A. marina leaf extracts collected from three Indonesian locations: Cilacap, Pontianak, and Sangihe. The total phenolic and flavonoid content, antioxidant activity, and metabolite profiles were assessed using spectrophotometric assays and Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS). Chemometric analyses were performed using Principal Component Analysis (PCA) and partial least squares discriminant analysis. The results showed that ethyl acetate leaf extracts of A. marina from Sangihe exhibited the highest levels of phenolics (13.811 mg GAE/g), flavonoids (76.179 mg QE/g), and antioxidant activity (0.556 µg/mL, 0.249 µg/mL, and 0.232 µg/mL) using three different methods. LC-HRMS detected 618 metabolite compounds. PCA showed clear clustering patterns among the sample groups, with two principal components: PC1, which explained variation by extraction technique, and PC2, which explained variation across ecological and genetic regions. These results indicate that environmental conditions and solvent types influence the type of metabolite compounds. Specific compounds such as 3-(decylsulfonyl)-5 and 8-tetradecadiene were predominant in samples from Pontianak, and lactucaxanthin (a carotenoid) was abundant in samples from Sangihe. These chemometric findings highlighted the ecological and pharmacological importance of A. marina and provided a foundation for future research on bioactive compound development and environmental metabolomics of tropical mangrove species.